[INVITED] A miniaturized optical fiber microphone with concentric nanorings grating and microsprings structured diaphragm. (April 2016) - Wang, Hui; Xie, Zhenwei; Zhang, Mile; Cui, Hailin; He, Jingsuo; Feng, Shengfei; Wang, Xinke; Sun, Wenfeng; Ye, Jiasheng; Han, Peng; Zhang, Yan
Abstract: A miniaturized optical fiber microphone (OFM) is created by fabricating a concentric nanorings grating and microsprings structured half spherical diaphragm on the end facet of a single-mode fiber (SMF). The diaphragm is fabricated via the method of two-photon 3D lithography. The thin nanorings grating patterned diaphragm is actually a resonant grating-waveguide. It exhibits high reflectivity when resonance is excited. A microlens is fabricated at the core of the fiber, which is used to diverge the output light to make it be normally incident onto the diaphragm, then reflected back to the fiber. The intensities of the reflected back light will be changed if the resonant conditions of the resonant grating-waveguide are broken due to the sound pressure induced geometrical changes of the configuration. This makes such device be an acoustic sensor. The microsprings are designed to improve the sensitivity to the sound pressure. Acoustic inspections show that this OFM can detect the weak sound in air with frequency band from 400 to 2000 Hz. Highlights: A miniaturized optical fiber microphone (OFM) is designed based on a 3D micro- and nanostructured half spherical diaphragm on the end facet of a single mode fiber. The diaphragm is fabricated via the method of two-photon 3D lithography. Resonant grating-waveguide, microlens and microsprings are combined together to improve the performance of the OFM.